2020
DOI: 10.1093/eurheartj/ehaa446
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and temporal trends in aortic dissection: a population-based study of incidence, treatment strategies, and outcome in Swedish patients during 15 years

Abstract: Abstract Aims As large population-based studies of aortic dissection are lacking, the incidence numbers and knowledge about time-trends and sex differences are uncertain. The objective was to describe incidence, temporal trends and outcome of aortic dissection with particular emphasis on sex differences. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
87
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 29 publications
11
87
2
Order By: Relevance
“…3 Moreover, female patients were older, had smaller aortic diameters less likely to smoke or have hypertension, and more likely to have diabetes mellitus and anemia. 1,8 In the present cohort, we found that the proximal landing zone for stent graft in 0 and 1 tended to be higher in males. Therefore, males were more likely to require aortic arch bypass.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…3 Moreover, female patients were older, had smaller aortic diameters less likely to smoke or have hypertension, and more likely to have diabetes mellitus and anemia. 1,8 In the present cohort, we found that the proximal landing zone for stent graft in 0 and 1 tended to be higher in males. Therefore, males were more likely to require aortic arch bypass.…”
Section: Discussionsupporting
confidence: 46%
“…28 Indeed, female patients who were surgically treated for TAAD had a higher mortality rate than male patients (31.9% vs 21.9%, P ¼ .013). 8 Meanwhile, 2 studies from Japan and Germany found that female sex was not an independent predictor of mortality after surgery for TAAD. 29,30 Several studies have reported no sex differences in shortterm outcomes for TBAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For untreated Standford type A of AAD, the mortality rate increased by 1-2% every 1 hour [3][4] . 30-day mortality in hospitalized patients with any acute aortic dissection was 37% [5] . Due to the rapid development of AAD and the high mortality rate, early diagnosis and progress evaluation are clinically important issues.…”
Section: Introductionmentioning
confidence: 97%
“…An acute aortic dissection is a medical catastrophe [ 1 ] with an estimated mortality of 26% in patients undergoing acute surgery and up to 58% in patients not receiving surgical treatment [ 2 ]. Reported incidences of an aortic dissection vary between 3 and 9 per 100,000 person-years [ 1 , 2 , 3 , 4 ], but with an aging population further increases are anticipated for the future.…”
Section: Introductionmentioning
confidence: 99%